The AEF Way of War The American Army and Combat in World War I - Grotelueschen, Mark Ethan (Cambridge University Press, 2013)
While critiquing northern and southern generalship in the American Civil War, the distinguished historian, T. Harry Williams, claimed that the war was not just a struggle of men and material but also “a war of ideas.”1 He was referring not only to the political or social ideologies then being contested between the northern and southern states but especially to the military theories and beliefs that guided the decisions of the leading generals on each side